Coastal Environments - Simionato, Claudia G. (2014)
working paper -- Universidad de Costa Rica. Centro de Investigaciones Geofísicas, 2014. Sugerencia para citar el documento: Simionato, C. G., E. Alfaro and R. Martinez, 2014. Summary community-based position paper on "Coastal environments", on the outcomes of the World Climate Research Programme (WCRP) Conference for Latin America and the Caribbean, Developing, Linking, and Applying Climate Knowledge. Montevideo, Uruguay, 17-21 March, 2014. Appendix 5, 28-31.